EXPERIMENTAL AND ANALYTICAL ANALYSIS OF PRE-STRESSED CONCRETE SPLICED GIRDER MODELS (Journal of Engineering, 2009)
The present research is concerned with experimental and analytical studies of prestressed concrete spliced and non-spliced girder models. The test groups consisted of (16) girders of rectangular sections. Eight girders are spliced while the other eight are reference non - spliced girders. Each spliced girder is composed of three concrete segments connected by splices of ordinary reinforced concrete with hooked dowels different locations. The tested girders were of single span or continuous over intermediate supports. For single span girders two splices were used and post-tensioning was carried out for the full assembled girder. For the continuous girders pre-tensioned segments were connected by splices at quarter spans.Concentrated or uniformly distributed loads have been applied to the girders. The deflection was measured at mid-spans while the strain was measured at splice zones and at mid-spans.Nonlinear analysis of the girders was carried out using a modified computer program. A comparison among the experimental and the analytical results for spliced and non-spliced girders was carried out to study the effects of splicing for different girders. Results have shown that at about 50% of the ultimate load which is approximately corresponds to the serviceability limit state, the deflection of the spliced girders is greater than that of the reference non-spliced girders in the range of (10%-15%) and the ultimate loads for the nonspliced girders are greater than those of the spliced girders in the range of (12%-17%). The difference in deflection between the Finite Element and the experimental results at 50% ofthe ultimate load was in the range of (8%-12%). Moreover, the difference in the ultimate load between the Finite Element and the experimental results was in the range of (5%-11%).